The Role of the Hippocampus in Avoidance Learning and Anxiety Vulnerability - Cominski, Tara P.; Jiao, Xilu; Catuzzi, Jennifer E.; Stewart, Amanda L.; Pang, Kevin C. H. (Frontiers in Behavioral Neuroscience, 2014)
The hippocampus has been implicated in anxiety disorders and post-traumatic stress disorder (PTSD); human studies suggest that a dysfunctional hippocampus may be a vulnerability factor for the development of PTSD. In the current study, we examined the effect of hippocampal damage in avoidance learning, as avoidance is a core symptom of all anxiety disorders. First, the effect of hippocampal damage on avoidance learning was investigated in outbred Sprague Dawley (SD) rats. Second, the function of the hippocampus in Wistar-Kyoto (WKY) rats was compared to SD rats. The WKY rat is an animal model of behavioral inhibition, a risk factor for anxiety, and demonstrates abnormal avoidance learning, marked by facilitated avoidance acquisition and resistance to extinction. The results of the current study indicate that hippocampal damage in SD rats leads to impaired extinction of avoidance learning similar to WKY rats. Furthermore, WKY rats have reduced hippocampal volume and impaired hippocampal synaptic plasticity as compared to SD rats. These results suggest that hippocampal dysfunction enhances the development of persistent avoidance responding and, thus, may confer vulnerability to the development of anxiety disorders and PTSD.